👤

please solve this.
1. 2(×+5) - 7 = 3 (x-2)​


Sagot :

[tex]\red{⊱┈────────────────────┈⊰}[/tex]

PROBLEM :

  • 2(×+5) - 7 = 3 (x-2)

===========================================

ANSWER :

  • [tex]\red{\boxed{ \red{\boxed{ \sf x=9 }}} }[/tex]

===========================================

SOLUTION :

[tex] \\ [/tex]

Let's use distributive property to multiply 2 by x + 5

  • [tex]\tt{ 2x+10-7=3\left(x-2\right) }[/tex]

  • [tex]\tt{ 2x+3=3\left(x-2\right) }[/tex]

  • [tex]\tt{ 2x+3=3x-6 }[/tex]

  • [tex]\tt{ 2x+3-3x=-6 }[/tex]

  • [tex]\tt{ -x+3=-6 }[/tex]

  • [tex]\tt{ -x=-6-3 }[/tex]

  • [tex]\tt{ -x=-9 }[/tex]

[tex] \\ [/tex]

lastly, multiply both sides by -1,so therefore the possible answer is [tex] \tt\red{\underline{ \: x=9 }}[/tex]

[tex]\red{⊱┈────────────────────┈⊰}[/tex]

#CarryOnLearning

[tex]\begin{gathered}\tiny\boxed{\begin{array} {} \red{\bowtie} \:\:\:\:\:\:\: \red{\bowtie}\\ 。◕‿◕。 \\ \end{array}}\end{gathered}[/tex]

ꨄ︎